Islam and quantum theory: from signs or symbols to science - Akdogan, Cemil (s.n, 2012)
Islam and quantum physics are compatible due to a shared phenomenological approach which denies that we can know the substance of anything or that matter has a substance at all. In other words, both entirely depend on "Ayat" (sign), appearances (phenomena) or symbols that cannot have any substance or corresponding reality as independent, material entities in the external world. It is through the elimination of material substance that human consciousness has gained its pivotal and fundamental position and placed science into its proper place